Carbon dioxide capture using bi-blended and tri-blended amines solution in packed bed absorber - Abdullah, Noor Taha; Shakir, Ibtehal K.; Al-lami, Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Carbon capture and storage technologies are crucial in mitigating greenhouse gas emissions. This study investigates the enhancement of CO2 absorption through refining amine blends, specifically diethylenetriamine (DETA) with monoethanolamine (MEA) and tetraethylenepentamine (TEPA) with MEA at different concentrations and employing chemical promoters to boost the performance of the gas treatment system. The behaviour of these amines was evaluated by the impact of mixing DETA and MEA across different concentrations. The results showed that the removal efficiency increased with increasing DETA concentration. Similarly, the TEPA-MEA blend was investigated, demonstrating an increase in removal efficiency with increasing TEPA concentration. Removing efficiency improved from 75% with 30% MEA to about 96% with a 15% MEA and 15% TEPA mixture while maintaining the absorption rate due to the sufficient column height. Also, the study explores the effect of utilizing chemical promoters, specifically piperazine (PZ), potassium carbonate (K₂CO₃), and benzylamine (BZ), when combined with 15 % MEA and 10% DETA to boost the absorption rate and improve the CO2 loading capacity. The findings indicate that adding 5% BZ to the MEA-DETA solution increases removal efficiency by 10%. Moreover, adding 5% PZ to the same mixture increased efficiency by about 18%. Meanwhile, the volumetric mass transfer coefficient, KGav, more than doubled. Finally, the study examined the effect of using the same promoters with 15% MEA and 10% TEPA on CO2 capacity and mass transfer rates. The outcomes demonstrate that both removal effectiveness and KGav were dropped when using BZ and K₂CO₃ in the MEA-TEPA blend. The removal efficiency increased somewhat with PZ, but KGav was not significantly affected. In conclusion, the mass transfer rate and CO2 removal efficiency from flue gases will be enhanced by the use of bi-amines such as MEA-DETA and MEA-TEPA in chemical absorption. However, because they enhance the amine group in the absorbent, promoters such as PZ and BA can raise the carbon dioxide removal efficiency to an economically valuable level.